2019
DOI: 10.1038/s41598-019-45325-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Amelioration of obsessive-compulsive disorder in three mouse models treated with one epigenetic drug: unraveling the underlying mechanism

Abstract: Mental health disorders are manifested in families, yet cannot be fully explained by classical Mendelian genetics. Changes in gene expression via epigenetics present a plausible mechanism. Anxiety often leads to avoidant behaviors which upon repetition may become habitual, maladaptive and resistant to extinction as observed in obsessive compulsive disorders (OCD). Psychophysical models of OCD propose that anxiety (amygdala) and habits (dorsolateral striatum, DLS) may be causally linked. The amygdala activates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…One of the aims of the future work at the Bergen Center for Brain Plasticity is to combine MRI and other biological measures to a contribute to a more integrated view of the psychobiology of OCD and anxiety disorders. We also aim to combine these measures with genetics and epigenetics to better understand how changes in the body and brain are reflected in DNA and its methylation (Todorov, Mayilvahanan, Ashurov, & Cunha, 2019).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…One of the aims of the future work at the Bergen Center for Brain Plasticity is to combine MRI and other biological measures to a contribute to a more integrated view of the psychobiology of OCD and anxiety disorders. We also aim to combine these measures with genetics and epigenetics to better understand how changes in the body and brain are reflected in DNA and its methylation (Todorov, Mayilvahanan, Ashurov, & Cunha, 2019).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Two knock-out mice models that generated a phenotype replicating the features observed in patients showed a phenotype very similar to the OCD features observed in patients: the SAPAP3-/- (Welch et al, 2007) and the SLITRK1-/-mice (Katayama et al, 2010), exhibiting increased anxiety and compulsive grooming behaviors. Todorov et al (Todorov et al, 2019) observed that inhibition of DNA methyltransferase in these mice induced marked symptom improvement lasting for at least one week, as well as reversed altered methylation of protein phosphatase 1 gene, which inhibits memory formation and learning (Genoux et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic pruning might also be altered in mice intranasally infected with Group A Streptococcus, which function as a model for PANDAS (Paediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections, characterized by sudden onset OCD) [ 54 , 55 ]. Moreover, the offspring of pregnant Sapap3 ko mice injected with the non-nucleoside DNA methyltransferase inhibitor RG108, which affects synaptic pruning, showed a 4-month delay in the development of repetitive grooming behaviour [ 56 ], whereas a similar injection in adult Sapap3 ko mice ameliorated such behaviour for only 3 days [ 57 ]. Parallel, a series of clinical imaging studies suggest abnormal synaptic pruning patterns in, among others, frontostriatal brain structures as a possible explanation for volumetric abnormalities in paediatric OCD patients [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%